Antifungal activity of Vietnamese essential oils against dermatophytes fungi - Nguyen , Van Khanh; Truong, Thi Yen Nhi; Nguyen , Duy Nien; Nguyen , Canh Nhat; Do , Thi Bich Thao; Ngo, Thi Minh Chau (Tạp chí Y Dược Huế, 2026)
Background: Dermatophytosis is a prevalent disease with high incidence reported in tropical countries such as Vietnam. Currently, there are not many available types of antifungal drugs for dermatophytosis, and prolonged treatment is usually required. Besides, drug resistance in dermatophytes is a major concern in dermatology practice, especially that of Trichophyton indotineae. Objectives: Evaluating the antifungal activity of some local natural essential oils from Vietnam, mainly from Hue City, against species of dermatophytes belonging to genera Trichophyton, Microsporum, and Nannizzia. Materials and Methods: Essential oils including Melaleuca cajuputi, Citrus grandis var. Thanh trà, Cinnamon, Cymbopogon citratus, and Mentha arvensis L were tested. The essential oils were diluted with RPMI medium at various concentrations and then cultured with 16 dermatophyte strains of Microsporum canis, Nannizzia incurvata, Trichophyton indotineae, Trichophyton interdigitale, and Trichophyton rubrum to determine Minimum Inhibitory Concentrations (MICs) of these essential oils after three, five and seven days following EUCAST guidelines version 11.0. Results: All tested essential oils exhibited antifungal activity against dermatophyte species. The MIC of Cymbopogon citratus (0.05 - 0.08%) was significantly lower than the values of Laurus cinnamomum (cinnamon) (0.1 - 0.18%), Mentha arvensis L. (0.19 - 0.5%), Melaleuca cajuputi (0.43 - 0.99%), and Citrus grandis var. Thanh trà (0.52 - 1.09%) (p < 0.001). Laurus cinnamomum (cinnamon) oil also proved better inhibitory ability than the other three oils; Mentha arvensis L. oil demonstrated lower MIC than Citrus grandis and Melaleuca cajuputi oil (p < 0.01). Data analysis showed that Cymbopogon citratus, Cinnamon, and Mentha arvensis L. oils maintained stable MIC values over 3 and 5 days, but increased MICs on the 7th day, meanwhile Citrus grandis oil MIC values, despite being high, remained unchanged from the 5th to 7th day. Regarding T. indotineae, the strains were inhibited by Mentha arvensis L., Cymbopogon citratus, and Cinnamomum oils, all of which maintained MIC values within 0.2% over 7 days of incubation. Conclusion: This is the first study in Vietnam to evaluate antifungal activity of essential oils against dermatophyte strains. All essential oils demonstrated antifungal activity against dermatophyte species. Cymbopogon citratus, Mentha arvensis L, Cinnamon, Citrus grandis var. Thanh trà are potential candidates for further research.